kerukunan Hidup Umat Beragama dalam Perspektif Islam - Sirajuddin Zar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
Got tolerance in Islam should be practiced and developed by the Muslims themselves. We are as Muslim s very fortunate with the differences in the understanding of Islam. That difference has been the will of God because God created man different level of intelligence. The results that we have adopted any of ijt ihad in Islam does not contradict the Qur’an and hadith will not bring out of Islam. Religious harmony does not want to unite all religions, or not to generalize all religions, or want to create a new religion combine d from all religions. But we want to try is to attempt to build bridges with the harmonious relationship among religions.